2016 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2016
DOI: 10.1109/iros.2016.7759827
|View full text |Cite
|
Sign up to set email alerts
|

Gust disturbance alleviation with Incremental Nonlinear Dynamic Inversion

Abstract: Abstract-Micro Aerial Vehicles (MAVs) are limited in their operation outdoors near obstacles by their ability to withstand wind gusts. Currently widespread position control methods such as Proportional Integral Derivative control do not perform well under the influence of gusts. Incremental Nonlinear Dynamic Inversion (INDI) is a sensor-based control technique that can control nonlinear systems subject to disturbances. This method was developed for the attitude control of MAVs, but in this paper we generalize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 15 publications
0
55
0
Order By: Relevance
“…The velocity of the Cyclone can be controlled by controlling the linear acceleration of the vehicle. This can be done by applying the INDI methodology, as we have shown in a previous paper [21]. In that paper, we showed that increments in linear acceleration can be achieved by increments in the thrust vector of a multirotor helicopter.…”
Section: Velocity Controlmentioning
confidence: 79%
See 1 more Smart Citation
“…The velocity of the Cyclone can be controlled by controlling the linear acceleration of the vehicle. This can be done by applying the INDI methodology, as we have shown in a previous paper [21]. In that paper, we showed that increments in linear acceleration can be achieved by increments in the thrust vector of a multirotor helicopter.…”
Section: Velocity Controlmentioning
confidence: 79%
“…The guidance of an INDI controlled quadcopter was described in previous research [21], and as INDI acceleration control is providing an abstraction layer, the Cyclone can be controlled in the same way. It starts from a certain position error, which multiplied with a gain produces the desired velocity vector.…”
Section: Guidancementioning
confidence: 99%
“…This paper is an extension to the work presented at the Intelligent Robots and Systems conference [17]. Differences include: (1) the use of a large open jet windtunnel as a more accurate and more powerful disturbance than the fan used previously.…”
Section: Introductionmentioning
confidence: 99%
“…The control of the horizontal position during the hover phase is done with an incremental nonlinear dynamic inversion (INDI) controller. A detailed description of this control method, along with experiments that show the performance, is provided in previous work (Smeur, de Croon, & Chu, ). The rationale behind this controller is that the accelerometer measurement provides the sum of forces acting on the vehicle.…”
Section: Controlmentioning
confidence: 99%